Tipificações da instituição do divórcio sob as lentes do jornal Folha de S. Paulo entre 1970-1980 - Ortis, Andréa Corneli (2023)
This research questions how the typifications about the institution of divorce are constructed in the Folha de S. Paulo newspaper through the mediations between the lived and recorded culture. Therefore, our general objective is to analyze how the newspaper Folha de S. Paulo mediates the representation and construction of divorce typifications in its reports published between 1970 and 1980 in relation to the lived and recorded culture. As specifics, we intend to: map the elements of the historical, political, economic and social context of global and Brazilian feminism and the institution of divorce, present during the transmission of the reports; observe narrative elements that form the discourse in the analyzed reports in order to verify how divorce was portrayed, if it was reinforced and/or silenced, as well as if it had a position contrary to feminist claims; and to identify the typifications of the institution of divorce in the newspaper Folha de S. Paulo. For this, we seek, through the elaboration of our own methodological path, based on the theoretical perspective of cultural studies, to observe our object through two great instances: lived culture and recorded culture inspired by Johnson's propositions (2006). These two instances are constantly mediated, according to Williams (1979), Martín-Barbero (1997) and Orozco Gómez (1997) and, thus, act as interpreters of everything that passes between them, which would result in typifications (WILLIAMS, 1979) of the institution of divorce in Brazil. We can see that women's struggles for recognition are constant and span centuries, after all, gender parity is not yet a reality, especially in Brazil. And, in the 27 reports analyzed using the Content Analysis method, compiled by Laurence Bardin (2011), we found twelve categories, in which it is evident that the media representations of gender are based on ideas, meanings and stereotypes that permeate generations, being frequent themes that link women to men, as if they could not ask for separation, as they would not be able to survive without a man by their side. After these categorizations, we found three typifications: maintenance of the bond, dissolution of the bond and culture of the selective tradition, which are constructed through a comparison between ideas, values and beliefs arising from the lived and recorded culture.